Synthesis of anisotropic rod-like gold nanostructures in organic media (vol 133, 106, 2021) - Prasad, V. Bhagavatula L.; Sivasankaran, Prathap Chandran; Patel, Pitambar; Malekar, V. Pushpa; Maya, V. K.; Ramana, V. Chepuri (Journal of Chemical Sciences, 2021)

Synthesis of anisotropic rod-like gold nanostructures in organic media - Prasad, V, Bhagavatula L.; Sivasankaran, Prathap Chandran; Patel, Pitambar; Malekar, V, Pushpa; Maya, V, K.; Ramana, V, Chepuri (Journal of Chemical Sciences, 2021)
Synthesis of anisotropic rod-like gold nanostructures was carried out in chloroform employing a modified ascorbic acid derivative as a reducing agent in the presence and absence of seed particles. The seed particles and/or the chloroaurate ions were phase transferred to the organic media using n-octadecyl amine. High-resolution transmission electron microscopy analysis clearly revealed that the anisotropic structures are single crystalline in nature. The stabilization of certain crystallographic faces of anisotropic gold nanostructures by amines is invoked to explain the formation of these structures.